2020
DOI: 10.3390/cancers12020317
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Glycolytic Dependence as a New Target of Olive Leaf Extract

Abstract: Oleuropein (Ole), the main bioactive phenolic component of Olea europaea L. has recently attracted the scientific attention for its several beneficial properties, including its anticancer effects. This study is intended to investigate whether an olive leaf extract enriched in Ole (OLEO) may counteract the aerobic glycolysis exploited by tumor cells. We found that OLEO decreased melanoma cell proliferation and motility. OLEO was also able to reduce the rate of glycolysis of human melanoma cells without affectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 57 publications
2
41
0
Order By: Relevance
“…Experimental evidence has proven that exposure to an olive leaf extract enriched in oleuropein reduced proliferation and motility in different cancer cells, such as melanoma [ 112 ], colon carcinoma [ 113 ], breast cancer [ 114 ] and chronic myeloid leukemia [ 115 ]. These effects are due to metabolic inhibitory activity exerted by oleuropein that neutralizes the aerobic glycolysis exploited by tumor cells, revealing that it may be effectively used as a complementary anti-cancer therapy [ 112 ].…”
Section: Oleuropeinmentioning
confidence: 99%
“…Experimental evidence has proven that exposure to an olive leaf extract enriched in oleuropein reduced proliferation and motility in different cancer cells, such as melanoma [ 112 ], colon carcinoma [ 113 ], breast cancer [ 114 ] and chronic myeloid leukemia [ 115 ]. These effects are due to metabolic inhibitory activity exerted by oleuropein that neutralizes the aerobic glycolysis exploited by tumor cells, revealing that it may be effectively used as a complementary anti-cancer therapy [ 112 ].…”
Section: Oleuropeinmentioning
confidence: 99%
“…A recent study demonstrated that oleuropein could significantly reduce the viability of breast cancer cells, suggesting its potential as a promising herbal medication to treat cancers [111]. Another report revealed the activity of oleuropein in reducing the expression of GLUT1 and PKM2 in the glycolysis pathway, although the mechanism underlying this regulation was not elucidated [112]. Menendez et al reported that polyphenols, flavonoids and secoiridoids extracted from olive oil could significantly suppress FASN protein levels in HER2-overexpressing breast cancer cells, including HER2 gene-amplified SKBR3 cells and engineered HER2-overexpressing MCF-7 cells.…”
Section: Downregulation Of Fasn Through Activating Tyrosine Kinase Receptormentioning
confidence: 99%
“…The beneficial effects of EVOO is the result of the combination of functional components, such as fatty acid composition (with a high content of oleic acid) and wide minor bioactive constituents, among which polyphenols such as oleuropein from Olea europaea L. Several biological properties attributed to oleuropein, providing beneficial effects in the prevention of degenerative diseases, are mainly based on its antioxidant potential [12], but a recent review by Nediani et al [2] describes how oleuropein has multi-target activity including the anti-inflammatory [13], the anti-amyloid aggregation [14], anti-hypertensive [15], hypoglycemic [16], cardioprotective [17], autophagy inducer [18,19] and anticancer [20], also in combination with standard anti-cancer drugs [21]. In this context, the anti-proliferative and pro-apoptosis activity of oleuropein, in addition to its ability to reduce the glycolytic metabolism of different tumor types [22], it might represent an effective tool for complementary cancer therapy. Due to these biological and biomedical effects of oleuropein, special attention is devoted to the recovery, recycling, and upgrading of food waste, leaves and by-products for its use in agronomic, nutraceutical, and biomedical applications [23].…”
mentioning
confidence: 99%